Brand Image And Country Of Origin Effects On Consumer Behavior Towards Choosing Power Tools At PT. Link Hardware And Led - Ezky Tiyasiningsih; Indra Firdiyansyah; Nurul Yusyawiru; Lastri Anggi Fani (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The main purpose of this research is to determine the effect of the Brand Image and Country of Origin either as partial or simultaneous toward the attitudes of the consumer at PT. Link Hardware and LED. This research is a quantitative research where the subject of it was taken from over thirty employees of PT Link Hardware and LED. The data collection is using the questionnaires which have been tested for its validity and reliability. The result of it indicates that there is a positive and significant effect between the Brand Image and the consumer’s attitude. But then, there is also a positive and significant effect between the Country of Origin and the consumer’s attitudes.